Responsabilidade moral em Strawson: atitudes reativas e moralidade social - Alves, Lyon (Universidade do Vale do Rio dos Sinos, 2023)
P.F. Strawson (1919-2006), an analytic philosopher and Waynflete Professor of Metaphysical Philosophy at Oxford, became very influential in discussions on moral responsibility, especially because of his famous article Freedom and Resentment, in which he dialogues with two positions, namely the pessimists and optimists (roughly speaking, incompatibilists and compatibilists), who differ on the validity of the practices of punishment, condemnation and moral approval, from the centrality of the determinist thesis. Therefore, as proposed by both parties, the terms of the discussion center on responsibility, freedom, and determinism. However, Strawson wants to analyze the question in another ground, which he calls the “field of non-distanced relations”. From this common field of relations, he argues that the problem lies in the possibility of knowing something as a general thesis of determinism. To expose what he argues to be a misunderstood problem within his analytic context, Strawson wrote two articles: Freedom and Resentment (1960) and Social Morality and Individual Ideal (1961). In them, the London philosopher exposes everything he has to say on the subject of morality. The present dissertation aims to elucidate the connection between both of Strawson's moral articles in light of his philosophical conception, thus enabling the correct approach to what he argues to be the domain of non-distanced relations and the gap he identifies in both positions. The research method will be through bibliographical analysis of the following works: Freedom and Resentment, Social Morality and Individual Ideal, Analysis and Metaphysics: an introduction to philosophy and Skepticism and Naturalism: some varieties. The analyses allow us to assert that Strawson is interested in addressing an underlying problem within human relationships, and this is the outcome of his philosophical stance, which results in the reconsideration (reinterpretation) of historical philosophical problems. Therefore, both articles are part of a single movement, which is to consider moral responsibility as a complex triadic relationship (epistemology, ontology, and logic). In summary, it can be indicated that the thesis of reactive attitudes inserts a metaphysical reinterpretation to the question of responsibility, and that the author uses two terms, namely attitude and reaction, in order to explore the inadequate conceptual assumption that pessimists and optimists impose on the discussion.
Keywords: Responsabilidade moral; Moralidade; Atitudes reativas; Tríade departamental; Moral responsibility; Morality; Reactive attitudes; Departmental triad; ACCNPQ::Ciências Humanas::Filosofia